2014
DOI: 10.1152/ajpheart.00893.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of IκBα by calpain induces myocardial NF-κB activation, TNF-α expression, and cardiac dysfunction in septic mice

Abstract: Recent studies in septic models have shown that myocardial calpain activity and TNF-␣ expression increase during sepsis and that inhibition of calpain activation downregulates myocardial TNF-␣ expression and improves cardiac dysfunction. However, the mechanism underlying this pathological process is unclear. Thus, in the present study, we aimed to explore whether IB␣/NF-B signaling linked myocardial calpain activity and TNF-␣ expression in septic mice. Adult male mice were injected with LPS (4 mg/kg ip) to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
1
24
2
Order By: Relevance
“…The PD150606 dose used in our experiments is comparable to previously published data on intraperitoneal injections in mice (21) but lower than previously published data on intraperitoneal injections in rats (22). Since in our experiments PD150606 was administered intramuscular around soleus muscle the overall muscle concentration was sufficient to achieve the calpain inhibitory effects comparable to previously published data (21), (22). The control animals received equal volumes of 1% DMSO/saline vehicle solution.…”
Section: Animal Proceduressupporting
confidence: 81%
“…The PD150606 dose used in our experiments is comparable to previously published data on intraperitoneal injections in mice (21) but lower than previously published data on intraperitoneal injections in rats (22). Since in our experiments PD150606 was administered intramuscular around soleus muscle the overall muscle concentration was sufficient to achieve the calpain inhibitory effects comparable to previously published data (21), (22). The control animals received equal volumes of 1% DMSO/saline vehicle solution.…”
Section: Animal Proceduressupporting
confidence: 81%
“…In the current study, we revealed that calpain mediates TGF-β1 protein synthesis in the HLFs. Moreover, it has been reported that calpain mediates dendritic protein synthesis in hippocampal tissues and neurons [26], and induces higher expression of TNF-α mRNA and protein in myocardial tissues [27]. Tabata and colleagues reported that bleomycin induced increases of TGF-β1 mRNA, which was suppressed significantly by the administration of a calpain inhibitor [14].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were treated with calpain inhibitor, calpeptin for the first 14 days (days 0-14) or the last 14 days (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the bleomycin-induced model. The administration of calpeptin for the first 14 days or the last 14 days prevented bleomycin-induced pulmonary fibrosis equally (35.4% decrease, 31.3% decrease).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prolonged exposure of paclitaxel increases calpain activity in primary rat dorsal root ganglion (DRG) and human neuroblastoma cells (Boehmerle et al, 2007). Recent reports suggested that IkB/NF-kB signaling remains a potential link between myocardial calpain activation and TNF-a expression in mice, in which treatment with calpain inhibitor markedly decreases TNF-a mRNA expression and improves cardiac dysfunction (Li et al, 2009a(Li et al, , 2014. Calcium channels and ryanodine receptors induce reactive oxygen species (ROS)-mediated calpain activation in high glucose-stimulated cardiomyocytes and hyperglycemic hearts.…”
Section: Introductionmentioning
confidence: 99%